Study and Application on RF Conformance Testing of TD-LTE Base Station - Li Gui; Luohui Xia (Dianxin kexue)
Currently，1ong term evolution（LTE）technology has become the key to the evolution of the whole mobile communication network. The radio frequency（RF）performance of TD-LTE base station，which is the only element in 3GPP radio access network，directly affects coverage，capacity and quality of service of the entire network. Firstly，the system architecture of TD-LTE base station and the related RF testing standard were introduced. Then，on the basis of the research of TD-LTE RF conformance testing，the physical meaning and influence on the actual network deployment of the test items were analyzed. Finally，a feasibility scheme of the base station RF conformance testing was proposed，and the results of some testing items were evaluated.